Reading John Grisham's Bleachers with Foucault: lessons for sports retirement. Issue 2 (3rd May 2020) - Jones, Luke
ABSTRACT: This paper has explored how a sociological reading of John Grisham's short work of fiction Bleachers can shed light on the complexities of the coaching and sports retirement processes. The aim of this paper was to consider the "sociological insights" that Bleachers has to offer by reading the novel in companionship with the thoughts of French post-structuralist thinker Michel Foucault, specifically his disciplinary analysis from Discipline and Punish . This paper has also observed how the figure of Coach Eddie Rake in Bleachers can be considered as trope for retired athletes' unresolved feelings towards their former sport. In achieving these aims, this paper has considered how Bleachers, when read through a sociological lens, can act as a meaningful data source for those invested in learning more about the poorly understood phenomena of sports retirement, as well as the dangers of coaching practices that are overly reliant upon the disciplinary logic of sport.